‘A pleasingly blank canvas’: urban regeneration in Northern Ireland and the case of Titanic Quarter - Ramsey, Phil (Taylor & Francis, 2013)
The ongoing development of Titanic Quarter in Belfast, Northern Ireland, has already made significant changes to the area. The site on which the Titanic was built has been redeveloped as an area for tourism, business, education and the creative industries. The site has been developed following a significant inflow of private capital, and with the additional support of local government and public finance. This article outlines how economic and political forces have coalesced in Belfast to the point that the violent period of the ‘Troubles’ in Northern Ireland can be said to have created a ‘pleasingly blank canvas for regeneration’.